Balance Between Tooth Size and Tooth Number Is Controlled by Hyaluronan - Sánchez, Natalia; González-Ramírez, María Constanza; Contreras, Esteban G.; Ubilla, Angélica; Li, Jingjing; Valencia, Anyeli; Wilson, Andrés; Green, Jeremy B. A.; Tucker, Abigail S.; Gaete, Marcia (Frontiers in Physiology, 2020)
While the function of proteins and genes has been widely studied during vertebrate development, relatively little work has addressed the role of carbohydrates. Hyaluronan (HA), also known as hyaluronic acid, is an abundant carbohydrate in embryonic tissues and is the main structural component of the extracellular matrix of epithelial and mesenchymal cells. HA is able to absorb large quantities of water and can signal by binding to cell-surface receptors. During organ development and regeneration, HA has been shown to regulate cell proliferation, cell shape, and migration. Here, we have investigated the function of HA during molar tooth development in mice, in which, similar to humans, new molars sequentially bud off from a pre-existing molar. Using an ex vivo approach, we found that inhibiting HA synthesis in culture leads to a significant increase in proliferation and subsequent size of the developing molar, while the formation of sequential molars was inhibited. By cell shape analysis, we observed that inhibition of HA synthesis caused an elongation and reorientation of the major cell axes, indicating that disruption to cellular orientation and shape may underlie the observed phenotype. Lineage tracing demonstrated the retention of cells in the developing first molar (M1) at the expense of the generation of a second molar (M2). Our results highlight a novel role for HA in controlling proliferation, cell orientation, and migration in the developing tooth, impacting cellular decisions regarding tooth size and number.